1997
DOI: 10.1083/jcb.139.3.785
|View full text |Cite
|
Sign up to set email alerts
|

The Ras Target AF-6 Interacts with ZO-1 and Serves as a Peripheral Component of Tight Junctions in Epithelial Cells

Abstract: The dynamic rearrangement of cell–cell junctions such as tight junctions and adherens junctions is a critical step in various cellular processes, including establishment of epithelial cell polarity and developmental patterning. Tight junctions are mediated by molecules such as occludin and its associated ZO-1 and ZO-2, and adherens junctions are mediated by adhesion molecules such as cadherin and its associated catenins. The transformation of epithelial cells by activated Ras results in the perturbation of cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
208
6
4

Year Published

1999
1999
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 293 publications
(227 citation statements)
references
References 53 publications
9
208
6
4
Order By: Relevance
“…In contrast to our results, another group has reported that the AF-6 protein (s-afadin) binds to Factin, is present in MDCK cells and is localized at ZO by interacting with ZO-1 in MDCK cells (Yamamoto et al, 1997). We ®rst examined here which afadin is expressed in MDCK cells and then where the expressed protein is localized in this cell line.…”
Section: Introductioncontrasting
confidence: 93%
See 4 more Smart Citations
“…In contrast to our results, another group has reported that the AF-6 protein (s-afadin) binds to Factin, is present in MDCK cells and is localized at ZO by interacting with ZO-1 in MDCK cells (Yamamoto et al, 1997). We ®rst examined here which afadin is expressed in MDCK cells and then where the expressed protein is localized in this cell line.…”
Section: Introductioncontrasting
confidence: 93%
“…No maltose-binding protein (MBP)-fusion protein of the N-terminal, middle or C-terminal fragment of l-afadin bound to a glutathione Stransferase (GST)-fusion protein of the N-terminal fragment of ZO-1 immobilized on glutathione-Sepharose (data not shown), in contrast to the result reported by Yamamoto et al (1997). No MBP fusion protein of l-afadin bound to a GST-fusion protein of the cytoplasmic region of occludin (data not shown).…”
Section: Presence Of L-afadin In Mdck Cellscontrasting
confidence: 78%
See 3 more Smart Citations